Obligasi Daerah Dalam Kerangka Hukum Keuangan Negara - Dewi Kasih, Desak Putu; Purwanti, Ni Putu (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 3 No 2 (2018)DO - 10.24843/AC.2018.v03.i02.p14, 2018)
Bonds are long-term debt securities issued by companies or governments with a nominal value and a certain maturity period and are a type of long-term investment for investors, but for the government as the issuer of bonds is a debt that must be returned. The obligation to return the said debt creates uncertainty for investors if it considers the provisions of Article 49 Paragraph (4) of Law Number 1 of 2004 concerning State Treasury which stipulates that state / regional property is prohibited from being handed over to other parties as payment for bills to the central government /area. The purpose of this paper is to analyze and harmonize the provisions governing Municipal Bonds to achieve legal certainty. The discussion of this article uses a type of normative research, given the inconsistencies in the regulation of the issuance of municipal bonds which creates legal uncertainty in the community. The results obtained include the construction of regulation of regional bonds within the regional financial framework, both internally and externally. Furthermore, the regulation can provide legal protection to investors with a regulation that confirms the obligation of regional governments to settle obligations towards regional bond investors. Thus it can be concluded, the Normative Construction of regulation of regional bonds consists of general laws and regulations that are specific in nature, general arrangements are constructed as provisions that provide the basis for the legality of regulating regional bonds and the norms for regulating special regional bonds containing the technical requirements for issuing bonds in the form of provisions concerning requirements and procedures and legal protection for regional bond investors, law enforcement can be applied in the case of claims for compensation and the government's obligation to repay bonds issued, special provisions governing bonds.